NAT10 mediates TLR2 to promote podocyte senescence in adriamycin-induced nephropathy - Mingyang Hu; Linxiao Lv; Yuqi Lei; Min Chen; Sijie Zhou; Zhangsuo Liu (Cell Death and Disease)
Abstract N-acetyltransferase 10 (NAT10) is involved in regulating senescence. However, its role in glomerular diseases remains unclear. Therefore, this study aims to investigate the mechanisms by which NAT10 influences senescence and damage in an adriamycin (ADR)-induced nephropathy model. Senescence (p16 and p21) and DNA damage markers (γ-H2AX (ser139)) were assessed in ADR-induced nephropathy. NAT10 function was demonstrated using Remodelin or small interfering RNA (siRNA) interventions. Transcriptome sequencing was conducted to identify key downstream genes and pathways, while coimmunoprecipitation was performed to evaluate the relationship between NAT10 and toll-like receptor 2 (TLR2) expression. TLR2 overexpression or knockdown further validated its regulatory role in senescence. In ADR-treated mice, the expression levels of P53, P21, P16, γ-H2AX(S139) proteins were elevated, while those of WT-1 and nephrin were reduced. This effect was mitigated by Remodelin and siNAT10 administration. Transcriptome sequencing identified TLR2 as a key downstream gene, and coimmunoprecipitation, along with molecular docking models, confirmed its interaction with NAT10. TLR2 overexpression plasmid or siRNA was employed for recovery experiments. Together, the study findings suggest that NAT10 contributes to podocyte senescence and injury via interaction with TLR2. Further, it demonstrates that NAT10 alleviates ADR-induced podocyte senescence by interacting with TLR2, potentially through a P53-P21-dependent mechanism. Thus NAT10 could serve as a novel therapeutic target for treating podocyte senescence and proteinuric glomerulopathies.